Synthesis of Quinazoline Derivatives - Devi, Meenu; Kumari, Akriti; Yadav, Anjali; Kumar, Ashish; Dwivedi, Jaya; Kaur, Navjeet (Current Organic Chemistry, 2025)
Efficient synthesis of heterocyclic has always been a very important task in drug discovery. Most of the drugs contain heterocycles to provide an interface between chemistry and biology. Among the various heterocyclic compounds, quinazoline, a heterocyclic compound, offers multiple advantages like pyrimidine, pyridine, piperidine, imidazole, morpholine, quinoline, purine, etc. Many research groups have demonstrated numerous synthesis techniques to harvest the advantage of quinazoline. Therefore, it is necessary to understand the various aspects of the development techniques of quinazoline as industry-oriented application. Various methodologies have been recently developed for the formation of quinazoline moiety. In this review article, the synthetic methods of quinazoline derivatives are classified based on metal-catalysed and miscellaneous synthetic aspects.
Keywords: biological molecules